Forecasting Public Health Risks In Malaysia: Insights From Seir Modelling Of Infectious Diseases - Nuha Rahim; Sakinah Ali Pitchay; M. A.B. Sahbudin; Ilfita K. Sahbudin (Penerbit USIM Press, 2025)
Malaysian Journal of Science Health & Technology, Volume 11 Issue 1 Page (34–42)